TEKNOLOGI MICRO ELECTRO MECHANICAL SYSTEMS - Widodo, Slamet; Kristiantoro, Tony (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
In this paper described the technology Microelectromechanical systems (MEMS) was applied in several fields including biology, chemistry, physics, telecommunications, electronics, medical, defense and so forth. A microelectromechanical system (MEMS) is one of the components (devices) are relatively small (micro scale) consists of components (devices) micromechanical (like microgears, microlevers, etc.), which moves both in response to certain stimuli (sensors) or the initiative to perform certain tasks (actuators), and microelectronic components to obtain information from, or control, or motion. In a broader sense, associated with MEMS technology, including materials and processes required to make MEMS components, integration components to create MEMS devices (sensors, actuators, etc.) and applications that use the devices (device) MEMS. In addition, other microsystems such as microchemical reactors, microthermal systems and smart materials (such as shape memory alloy) are also sometimes included in "MEMS Technology" based on its utility in sensors or actuators or as a source of power, heat sink, etc. In civil and commercial applications, MEMS offer advantages in various fields such as automotive control and safety systems, communications, satellite control, medical equipment and health monitoring, however, non-MEMS devices are often already exists for this application. If development is a useful alternative to MEMS, MEMS devices either have to fill capability gaps, ie, whether it should perform new functions, perform the function better than can currently be done or cheaper, lighter or smaller than the current available devices. For commercial applications, it also must be economical, ie, there must be sufficient demand for new devices that will be profitable. Keywords: MEMS, applications, devices, sensors, actuators.